Feelings and Consumer Decision Making: The Appraisal‐Tendency Framework - Han, Seunghee; Lerner, Jennifer S.; Keltner, Dacher (Journal of Consumer Psychology, 2007)
This article presents the Appraisal‐Tendency Framework (ATF; Lerner & Keltner, 2000, 2001; Lerner & Tiedens, 2006) as a basis for predicting the influence of specific emotions on consumer decision making. In particular, the ATF addresses how and why specific emotions carry over from past situations to color future judgments and choices. After reviewing the main assumptions and the 5 main principles of the framework, 2 streams of research are presented. One stream addresses emotional carryover effects on the assessment of risk; the other addresses carryover effects on the assessment of monetary value. Because risk assessment and value assessment are fundamental psychological processes, understanding them has the potential to yield manifold implications for consumer judgment and decision making. The concluding sections highlight limitations and future directions of the framework.